2022
DOI: 10.21037/acs-2021-ami-111
|View full text |Cite
|
Sign up to set email alerts
|

Post-infarction ventricular septal rupture

Abstract: Coronary reperfusion therapies have led to a reduction in the incidence of mechanical complications of acute myocardial infarction (AMI), but the associated mortality of these complications has remained high.Ventricular septal rupture is the most common mechanical complication after myocardial infarction and occurs in approximately 0.21% with ST-segment elevation myocardial infarction and in 0.04% with non-ST-segment elevation myocardial infarction. Surgery is the only definitive treatment but it is associated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…Studies have shown that most VSD occurs 3-5 days after AMI. 3 The patients receiving drug therapy alone have a median survival time of 5 days; more than 75% of patients die within 12 days after the onset of VSD symptoms, with 93.6% of 30-day mortality rate, and 96.2% of longterm mortality rate. 4 Therefore, based on the experience, the Closure of ventricular septal perforation is the key to the treatment of post-AMI VSD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown that most VSD occurs 3-5 days after AMI. 3 The patients receiving drug therapy alone have a median survival time of 5 days; more than 75% of patients die within 12 days after the onset of VSD symptoms, with 93.6% of 30-day mortality rate, and 96.2% of longterm mortality rate. 4 Therefore, based on the experience, the Closure of ventricular septal perforation is the key to the treatment of post-AMI VSD.…”
Section: Discussionmentioning
confidence: 99%
“…In our report, the patient did not seek medical treatment. Studies have shown that most VSD occurs 3–5 days after AMI 3 . The patients receiving drug therapy alone have a median survival time of 5 days; more than 75% of patients die within 12 days after the onset of VSD symptoms, with 93.6% of 30‐day mortality rate, and 96.2% of long‐term mortality rate 4 .…”
Section: Discussionmentioning
confidence: 99%
“…Being the most common mechanical complication of MI [3], VSR is also one of the most lethal if left untreated, with a 50% survival rate after one week, 20% within one month and 10% within one year [1,3]. VSR is a consequence of loss of septal blood supply by branches derived from the left anterior descending artery from the left coronary and posterior interventricular branch from the right coronary (albeit in right dominant patients).…”
Section: Ventricular Septal Rupturementioning
confidence: 99%
“…Post-myocardial infarction (MI) ventricular septal rupture (VSR) is a rare but potentially catastrophic mechanical complication [ 1 ], which specifically occurs in 0.21 % of patients with ST-segment elevation myocardial infarction (STEMI) and 0.04 % of patients with non-ST-segment elevation myocardial infarction (NSTEMI) [ 2 , 3 ]. Post-MI VSR is a medical emergency with a mortality rate of 70 %–80 % during the 2 weeks following diagnosis, and guidelines recommend urgent surgical closure irrespective of the patient's hemodynamic status [ 1 ].…”
Section: Introductionmentioning
confidence: 99%